Flower colour and size-signals vary with altitude and resulting climate on the tropical-subtropical islands of Taiwan - Shrestha, Mani; Tai, King-Chun; Dyer, Adrian G.; Garcia, Jair E.; Yang, En-Cheng; Jentsch, Anke; Wang, Chun-Neng (Frontiers in Plant Science, 2024)
The diversity of flower colours in nature provides quantifiable evidence for how visitations by colour sensing insect pollinators can drive the evolution of angiosperm visual signalling. Recent research shows that both biotic and abiotic factors may influence flower signalling, and that harsher climate conditions may also promote salient signalling to entice scarcer pollinators to visit. In parallel, a more sophisticated appreciation of the visual task foragers face reveals that bees have a complex visual system that uses achromatic vision when moving fast, whilst colour vision requires slower, more careful inspection of targets. Spectra of 714 native flowering species across Taiwan from sea level to mountainous regions 3300 m a.s.l. were measured. We modelled how the visual system of key bee pollinators would process signals, including flower size. By using phylogenetically informed analyses we observe that at lower altitudes including foothills and submontane landscapes there is a significant relationship between colour contrast and achromatic signals. Overall, the frequency of flowers with high colour contrast increases with altitude, whilst flower size decreases. The evidence that flowers colour signaling becomes increasingly salient in higher altitude conditions supports that abiotic factors influence pollinator foraging in a way that directly influences how flowering plants need to advertise.